Supply and Demand Balance of Ecosystem Services in the Ulanbuh Desert - Weijia Cao; Xinyu Wang; Qingkang Yang; Huan Liu; Guoxiu Jia; Huamin Liu; Lixin Wang; Xuefeng Zhang; Lu Wen (Land)
Desert ecosystems play a critical role in global climate regulation. Current research reveals a relative lack of research regarding desert ecosystem service (ES) supply and demand. Therefore, we selected the Ulanbuh desert, one of the eight major deserts in China, as study area. Using specialized models, we quantify the supply and demand of four ES, including water yield (Wy), soil conservation (Sc), windbreak and sand fixation (Ws), and carbon sequestration (Cs), from 1985 to 2020. Univariate linear regression analysis and panel data analysis (PDA) were used to examine trends in desert ES supply–demand ratio (ESDR) and its determinants. The findings indicated that ES supply presented increases in Sc and Cs, and decline in Ws from 1985 to 2020. Demand patterns showed a growth trend for Wy and Cs. ESDR revealed that Sc, Ws, and Cs show an excess of supply over demand and are in a decreasing trend, while Wy displays a supply deficit relative to demand with no significant change. The comprehensive ESDR decreased over the study period, with a supply-deficit status emerging in the southwestern area. Natural factors (NDVI and precipitation) and socio-economic factors (GDP and population density) served as the main factors affecting the comprehensive ESDR. This research provides a novel perspective for desert ecosystems management and conservation, emphasizing the necessity of incorporating the ES supply and demand balance into regional development policies to achieve sustainable development in arid regions.